Integrating Analysis of Quality Management of Higher Education: Analytical Hierarchy Process and Multiple Linear Regression - Satria Abadi; Citrawati Jatiningrum; Samsurijal Hasan; Riki Riki (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
The study focus on to determine factors of the quality management on the higher education and analysis the effect of important factors of quality management. Factors of quality management in this study which covering of human resources, facilities and infrastructure, leadership, and organization. Sample study using students from several private universities in Lampung Province. Analysis method using integrating analysis by Analytical Hirarchy Method (AHP) and Multiple Regression Linear (MLR). Correlation test using the product moment stated quality management of higher education have a strong relationship to human resources, has a moderate relationship with infrastructures, and a weak relationship to the leadership and organizing. The result by multiple regression linear method reveal that significant effect on human resources, facilities and infrastructure, leadership and organizational on Quality Management in higher education. While, AHP method suggestion the result that the most important in Quality Management of Higher Education is a human resources owned by a higher education. This evidence contribute to the decision makers in universities which is priority and have to improve the quality of higher education management